Quality Intrapartum Care Experiences of Women and Midwives in Low- and Middle-Income Countries: A Critical Narrative Review - Katushabe, Eve; Maliki, Ayishetu Musa; Steen, Mary; Ndinawe, John Bosco (African British Journals, 2025)
Quality intrapartum care measures are essential for reducing avoidable maternal and newborn morbidity and mortality. One factor contributing to the high burden of maternal and newborn illness is inadequate care during the intrapartum period. There is a substantial amount of qualitative research detailing the experiences of women and midwives with intrapartum care. However, narrative reviews that concentrate on the experiences of women and midwives while utilizing and providing intrapartum care respectively in sub-Saharan African Low- to Middle-Income Countries (LMICs) are scarce, as far as the authors are aware. We aimed to retrieve evidence that supports women’s and midwives’ experiences with quality intrapartum care by conducting a critical review of the literature. The literature was searched from PubMed, Google Scholar, Cochrane Library, and Science Direct/Elsevier with studies between June 2014 and July 2024. Qualified midwives and pregnant and postpartum women were target populations for the review. Therefore, we undertook a critical narrative review to ascertain relevant evidence related to intrapartum midwifery care and women’s experiences—qualitative studies that focused on the views and experiences of women and midwives in low- and middle-income countries. This review article addressed the following questions: “What are the women’s experiences with health facility intrapartum care?” and “What are the midwives’ experiences while providing health facility intrapartum care?” The aim of the review was to collect, analyze and synthesize the low- and middle-income countries’ evidence that supports quality intrapartum care during first and second stages of labour, which will inform midwifery practice, education and future research, and positively influence this aspect of midwifery care for women. Out of the 250 retrieved studies, 12 met the inclusion criteria. Three themes and four subthemes were identified from the data: Theme one: Quality of care expectations with four subthemes; (1) Respectful, dignified care; (2) Availability of structural resources; (3) Cultural sensitivity; (4) Labour and pain relief. Theme two: Negative experiences with two subthemes; (1) Physical and verbal abuse; (2) Lack of communication and privacy. Theme three: Midwives’ perspective with two subthemes; (1) Midwives’ challenges and professional identity; (2) Impact on midwives. It was concluded that women and midwives work together as partners in the process of maternity care. In addition to addressing women's needs and rights, midwives are crucial in advancing women's rights and developing interpersonal relations. Further research is needed to explore both the users’ and providers’ experiences concurrently; this will enhance strategies aimed at improving the quality of intrapartum care in LMICs.